(3QSGdI efJNHI Ydi SHjd GdGNJUGQ ef cJGH GdMces - (3eMeO Hf eMeO Hf EHQGgje YeGQI GdLejMehfis; (3GdOefghQj , CMeO Hf YHO GdefYe Hf jhSa Hf UjGe GdOefghQj, SQGL GdOjf,J (B1192 (3g` s
(3ChdgG (B:s
(3GeG HYO agPg QSGdI efJNHI , Ydi SHjd GdGNJUGQ ef cJGH GdMce dTjN CMeO GdOefghQi , eQJHI Ydi GdMQha GdgLGFjI s
(3BNQgG (B:s
(3hbGd HYV GdSda GdCjGOi CjO HjVGA hgj jO NVQGA hgj GdecGaFI hjO ShOGA hgj GdefGA s
(3HBNQ UaMGJgG JYbjHIs
(3cGf GdeNJUQ MjkG SfI (B1255(3g`s
(3Jhai UGMH cJGH GdMce SfI (B1192 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs